A clinico laboratorial study of effect of chronic alcoholism on hematological picture and changes in peripheral smear - Sai Sandeep, Kedarisetty; Sri Meghana, Kankipati (International Journal of Research in Medical Sciences, 2025)
Background: Alcohol consumption is a widespread public health concern, significantly impacting immunological functions, increasing vulnerability to infections, and contributing to hematological disorders. Chronic alcoholics often experience notable changes in their blood profile, necessitating further investigation. Methods: This observational cross-sectional study was conducted over two months at Andhra Medical College, Vishakhapatnam. A total of 45 male subjects, aged 26 to 76 years, consumed alcohol for more than five years and averaged over ten drinks per week. Exclusion criteria included congenital hematologic disorders and ongoing chemotherapy. Blood parameters were assessed against standard values. Results: Key findings included decreased red blood cell (RBC) counts in 68.9% of subjects, with macrocytosis observed in 82.2%. Lymphocytopenia occurred in 60%, while thrombocytopenia was found in 35.6%. Neutrophil levels were elevated in 62.2% of the cohort. Notably, a significant decrease in mean corpuscular hemoglobin concentration (MCHC) and an increase in mean corpuscular volume (MCV) were documented, reflecting typical consequences of chronic alcohol exposure. Conclusions: Chronic alcoholism significantly alters the hematological profile, characterized by decreased RBC counts, thrombocytopenia, increased neutrophils, lymphocytopenia, and macrocytosis. These findings underscore the urgent need for tailored interventions and preventive measures to address hematological impacts among chronic alcohol consumers.